Evaluation of student’s performance on biopsychosocial model—Three-stage assessment using e-learning platform in a distant education program in family medicine - Hemavathi Dasappa; T A Lakshmi; Farah Naaz Fathima; Elizabeth Reji; J Hudson; M Kiran (Journal of Family Medicine and Primary Care)
Introduction: The three-stage assessment, which includes clinical, individual, and contextual assessment, is a person-centred clinical method (biopsychosocial model). This method can help students and clinicians to assess biopsychosocial factors of the patient in a systematic way. Aim and Objective of the Study: To assess student performance of ‘three-stage assessment-patient centred care method’ using a rubric among students enrolled for fellowship in family medicine program. Methodology: It is a cross-sectional interventional study done at St John’s Medical College after obtaining ethical clearance among the students of the fellowship in family medicine program batch 2023–24 and 2024–25, a total of 80 students. Results: Overall assessment mean is 19.3263 (maximum score is 26) and SD is 3.5157. The mean for the clinical assessment (6.9236, SD 1.1465) is better than individual (5.8333, SD 1.5151) and contextual assessment (6.3819, SD 1.7492). The mean score for the management plan is 12 and SD is 2.2966 (maximum score is 16). Conclusion: Student’s performance of clinical assessment is better than individual and contextual (psychosocial) assessment and management. Overall performance of students on three-stage assessment is poor.